ANALYSIS OF FACTORS AFFECTING POVERTY IN SUMATRA INDONESIA - Agus Tri Basuki; Arif Rahmandhika (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
This study aims to analyze the effect of minimum wage, investment, gross regional domestic product, and open unemployment on poverty. The data used to support this research is time series data for a period of 5 years, precisely from 2017 to 2021 from all provinces on the island of Sumatra. The analysis model uses a panel data regression model with a Fixed Effect Model approach. The results showed that the minimum wage variable had a negative and significant effect on poverty, while the investment variable had a positive and insignificant effect on poverty, then the gross regional domestic product variable was found to have a negative and insignificant effect on poverty, while the open unemployment variable had a positive and significant effect on poverty.